Variasi Genetik pada Rusa Sambar (Rusa unicolor) di Penangkaran, Kabupaten Penajam, Kalimantan Timur - Wirdateti Wirdateti; Bram Brahmantyo; Gono Semiadi; Andi Reksodihardjo (Universitas Atma Jaya Yogyakarta, 2010)
Sambar deer (Rusa unicolor) is the largest Indonesian deer species. The largest population of captivation is located at Penajam district, East Borneo (UPTD). First population was introduced in 1990 with four individuals. The use of molecular marker was aimed to identify and characterise the level of genetic diversity within the UPTD population as well as to identify a possible of botolneck population genetic status. This study discussed the relevance of the result for management purposes of captivation. The results indicated that sambar deer populatin (n=38) had an average genetic distance (d) in population as 0.006 with nucleotide diversity (π) being 0.0159). A total of 43.48% of the population was homogeneous that showed no nucleotide differences among individuals.